Wasathiyah Values in the Hadith and Their Implementation in Education - Hasfiana, Hasfiana; Ahmad, Arifuddin; Maidin, Muh. Sabir (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The rise of religious and societal extremism deviates from Islamic precepts of moderation and balance. However, educational institutions often fail to teach wasathiyah (religious moderation), especially those derived from the Prophet's Hadith, the second source of Islamic law. Such behavior raises concerns about a severely or unlimitedly liberal generation. This study intends to completely identify the Prophet's Hadith values of wasathiyah, examine their significance to current education, and develop a model for applying these values in the curriculum and educational activities. This study is qualitative and library based. Thematic (maudu'i) and content analysis were used to assess authentic Hadiths that clearly or implicitly include wasathiyah values. The analysis results were integrated to create an education idea. The Prophet's Hadith contained wasathiyah values, including balance (tawazun), forbearance (tasamuh), fairness ('adalah), contemplation (shura), and ease (taysir). These values can be implemented in education through the integration of religious and general subjects, a dialogical and inclusive school culture, and wasathiyah teacher training. This study, from the Prophet's Hadith, provides a theoretical basis for wasathiyah in Hadith and Islamic education. Practically, this study can help educational officials, school principals, and instructors construct curricula and learning methodologies to produce moderate, tolerant, and balanced kids in thinking and behavior.